ChemInform Abstract: EGB‐Promoted Electrochemical Synthesis of 6‐Thioxo‐[1, 3, 5]‐triazinane‐2, 4‐dione Derivatives. Issue 39 (September 2016) - Sbei, Najoua; Haouas, Baya; Boujlel, Khaled; Batanero, Belen; Benkhoud, Mohamed Lamine
Abstract: Electrogenerated cyanomethyl base, obtained from electroreduction of neat acetonitrile, assists the reaction between thiourea derivatives (I) and isocyanates (II) furnishing the title triazinone derivatives (III).